2015
DOI: 10.1109/jsen.2015.2435025
|View full text |Cite
|
Sign up to set email alerts
|

Nonreciprocal Phase Error Caused by Orthogonal Magnetic Field in a Polarization-Maintaining Fiber-Optic Gyro

Abstract: This paper aims to investigate the nonreciprocity caused by orthogonal magnetic field (OMF) vertical to the light direction propagating in a polarization-maintaining fiber-optic gyro (PM-FOG). In orthogonal magnetic field, the nonreciprocal phase error (NPE) results from the small change of the propagation constants of the two opposite light waves propagating in the fiber coil. Even using a PM fiber coil, the pressure, twist and other imperfections will change the polarization state, which may lead to an insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…The light of ccw direction transmits through the optical path system, which is recorded as E − . E + can be expressed as [20], [14]…”
Section: Axial Magnetic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The light of ccw direction transmits through the optical path system, which is recorded as E − . E + can be expressed as [20], [14]…”
Section: Axial Magnetic Fieldmentioning
confidence: 99%
“…While, the influence of magnetic field is another important factor for IFOG and the research on magnetic field is still on primary stage. The magnetic field will produce a Faraday effect-induced bias error on the fiber coil [14], [15], [16], and the drift is difficult to distinguish form rotation velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, when both θ 1 and θ 2 are 90°, the light beams are propagated in the y polarization mode. The PM fiber coil, which is the main source of Faraday effect-induced bias error [ 18 ], is surrounded by the radial magnetic field H and temperature field T. The magnetic field is perpendicular to the sensitive axis of the PM fiber coil. The fiber with random twist is divided into micro-length unit dz .…”
Section: Theorymentioning
confidence: 99%
“…Although the Faraday effect is weak in silica, it is strong enough to be troublesome in the high-sensitivity IFOG [ 17 ]. For a polarization maintaining IFOG (PM-IFOG), the typical magnetic sensitivity is on the order of 10°/h/mT, well above the navigation-grade requirement of 0.1°/h/mT [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The TMOE originates from a magnetically induced lateral shift of the fiber mode [6]. Zhang et al [7] found that the TMOE in PMF-FOGs is not only curve-radius related, but it is also related to the polarization state of the light, errors in coupling angles between the pigtails of multifunction integrated optic circuit and the PMF coil, the pressure in fiber coil, and the twist rate of the fiber [8]. The Faraday nonreciprocal error grows as the square root of the length of the coil [3], whereas the TMOE is proportional to the number of turns in the coil, i.e., the ratio of the length over the diameter of the coil [6].…”
Section: Introductionmentioning
confidence: 99%